PEACE TREATIES IN THE 21st CENTURY: TREATY VALIDITY AT THE CROSSROADS OF THE PRINCIPLE OF PEACEFUL SETTLEMENT OF DISPUTES AND THE PROHIBITION OF THE USE OF FORCE - Szalai, Anikó (Pravni zapisi, 2026)
Peace treaties remain the central instruments of war termination, yet their legal nature is under-theorized in light of the UN Charter’s prohibition of the use of force and the duty of peaceful settlement. This article traces the historical evolution of peace treaties, analyzes their changing subject matter and third-party involvement, and examines how the Vienna Convention on the Law of Treaties (VCLT) regulates their conclusion and validity. Focusing on coercion and jus cogens, it argues that Articles 52, 53 and 75 VCLT, read together with the Charter regime, delegitimize results of aggression while preserving room for stabilising peace settlements. Drawing on Security Council practice and selected post-Cold War agreements, the article shows why states almost never invoke treaty invalidity against peace treaties and proposes criteria for distinguishing lawful stabilization from impermissible consolidation of aggression.